Study on electron beam transverse emittance at the linac-based THz laboratory in Thailand - K. Kosaentor (2018)
Copyright © 2016 CC-BY-3.0 and by the respective authors. This research focuses on simulations of transverse emittance of electron beams, which are produced from a linac-based THz source at the Plasma and Beam Physics (PBP) Research Facility, Chiang Mai University (CMU), Thailand. The accelerator system consists of a thermionic RF-gun, an alpha magnet, a linear accelerator, beam focusing and steering elements and various beam diagnostic instruments. The quadrupole scan technique is utilized to measure the transverse beam emittance at three main locations, which are downstream the RF-gun, the alpha magnet and the linac. The experimental setup consists of quadrupole magnets with a maximum gradient of 7.01 T/m, a drift tube, and a movable fluorescent screen station. Beam dynamic simulations by using the computer codes ELEGANT are performed to track electrons from the cathode to the experimental stations. In this contribution, the simulation results for the transverse emittance at various positions of the accelerator are reported and discussed.